SEXUAL CHANGES AND RELATED SEXUAL FACTORS IN PRIMIPARA MOTHERS DURING 3 TO 6 MONTHS POSTPARTUM 1384 - B. Anise; S. Tavoni; Z. Ahmade; F. Hosseini (Iran University of Medical Sciences, 2005)
Sexual intimacy and function is crucial in family structure and also the culture. In postpartum period some factors such as hormonal, physiological and psychological instability may impose sexual relation of the couples. Assessing the sexual function changes in primipara women and detection of the related factors, we performed a correlational study in which 460 mothers and their health husbands, all were selected by consequence sampling method were the participants. By using chi-square and Fisher exact test, finding showed that there were significant correlation between: 1) sex libido and previous dyspareunia and time of assumption of intercourse, pain and distress in first intercourse after delivery, dispareunia after delivery, 2) sex satisfaction and pain and distress in first intercourse after delivery, dispareunia after delivery, number of intercourse in week during 3-6 months after delivery, 3) sex pleasure and previous dyspareunia and pain and distress in first intercourse after delivery, dispareunia after delivery, 4) orgasm and previous dyspareunia and time of assumption of intercourse, pain and distress in first intercourse after delivery, dispareunia after delivery. (P=0/000-0/004). Over all, The results of the logistic regression test showed that there was no related factors with libido and sexual satisfaction, On the other hand, we found relations between changes in the level of sexual pleasure and the fear of first intercourse after delivery, the changes of the orgasm and the time of assumption of the intercourse, (with 30 days after delivery), the fear of first intercourse after delivery and eventually pain during intercourse. Taking a look on the results of this research, we can conclude that there is a need for teaching sessions for pregnant women before and after delivery, and the researcher also suggest consult clinics to be established for providing information and solving the problems.